2022
DOI: 10.1177/13567667221090991
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting consumers’ impulsive buying behavior in tourism mobile commerce using SEM and fsQCA

Abstract: Transactions through mobile commerce for tourism-related products and services are increasing. This phenomenon can lead to impulse buying due to technological features and personal inclinations. However, few studies have shed light on the phenomenon empirically. The purpose of this study is to investigate what motivates buyers to purchase tourism products through mobile commerce and how these motives impact consumers’ impulse buying behavior. First, we interviewed participants to study their motivation for mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 82 publications
1
18
0
Order By: Relevance
“…Moreover, in the mobile commerce context, financial incentives (e.g. discounts) rank among the most salient reasons why consumers use services provided by mobile commerce applications (Hanafizadeh et al, 2014;Um et al, 2022). Similarly, in the food delivery industry, many companies have focused on enhancing consumer perceived service value by reducing the prices of services and providing convenient communication via food delivery applications (Luu et al, 2016;Ahn and Kwon, 2021).…”
Section: Utility Theorymentioning
confidence: 99%
“…Moreover, in the mobile commerce context, financial incentives (e.g. discounts) rank among the most salient reasons why consumers use services provided by mobile commerce applications (Hanafizadeh et al, 2014;Um et al, 2022). Similarly, in the food delivery industry, many companies have focused on enhancing consumer perceived service value by reducing the prices of services and providing convenient communication via food delivery applications (Luu et al, 2016;Ahn and Kwon, 2021).…”
Section: Utility Theorymentioning
confidence: 99%
“…Also, in an investigation develop a ranking model to rank the CRs in mobile apps and this model upgraded the product quality in this market. Um et al (2022) in their research determined the motivator factors that lead to buying intention through MAs. They also shed light on how these make buying behavior structure by investigating the influential relationship.…”
Section: Mamentioning
confidence: 99%
“…The summary of study sources and the research gap is demonstrated in Table 2. 2021), (Tobing, 2015), Carvajal-Trujillo et al (2021), Lai (2015), Rasinger et al (2007), Um et al (2022), Kennedy-Eden and Gretzel (2021), Chen & Tsai (2019) , Alalwan (2020), Widarti and Emanuel (2020), Li and Xiao (2020) In this section, the methodology applied in the present study is presented. The methodology starts with data collection, preparation and distribution of questionnaires, and how to select the respondents and interviews with experts.…”
Section: Crs In Masmentioning
confidence: 99%
“…Overall, fsQCA has been applied to a variety of consumer behavior research topics, such as buying decisions, social media usage, mobile applications, smart technologies (e.g., chatbots), e-commerce, m-commerce, luxury shopping, sustainable consumption, and hospitality and tourism. Among these, buying decisions (e.g.,Septianto & Chiew, 2018;Xu et al, 2022), sustainable consumption (e.g.,Kopplin & Rösch, 2021;Onat et al, 2016), and hospitality and tourism(Manosuthi et al, 2022;Um et al, 2022) have been addressed the most using fsQCA. The following section highlights the major themes regarding the fsQCA application in consumer research.RQ2 aimed to identify the major themes emerging within consumer research specific to fsQCA.…”
mentioning
confidence: 99%
“…Researchers have, hence, focused on specific niches such as tourism(Johansson & Kask, 2017;Mathew & Soliman, 2021), fashion(Dabas & Whang, 2022;Ferreira et al, 2021), hospitality(Dabas & Whang, 2022;Elhoushy & Lanzini, 2021), retail(Lavoye et al, 2021;Ziaie et al, 2021), and many more for understanding specific consumer behavioral patterns and shifts. The studies reviewed within the present research also recommended using fsQCA in examining niche-specific consumer behaviors (e.g.,Das & Jebarajakirthy, 2020;Kopplin & Rösch, 2021;Um et al, 2022). Additionally, Li et al (2022) used fsQCA for understanding luxury brand purchases.…”
mentioning
confidence: 99%